Peran Niat Berperilaku dalam Memediasi Perilaku Pengelolaan Keuangan Keluarga - Jati, Agustinus Kismet Nugroho (Ekonomis: Journal of Economics and Business, 2025)
This study aims to analyze the influence of financial attitudes, self-control, spiritual intelligence, financial literacy with behavioral intentions as mediating variables. The population used is all people domiciled in Solo and Yogyakarta. The sample was selected using the purposive sampling method. The questionnaire was distributed online and offline. The results of the study indicate that financial attitudes, self-control, spiritual intelligence and financial literacy have a positive effect on family financial behavior. This study also found that behavioral intentions are able to mediate the influence of financial literacy with family financial management behavior.